Endophytic infection increases the belowground over-yielding effects of the host grass community mainly by increasing the complementary effects - Qu, Yaobing; Qin, Tianzi; Zhang, Junzhen; Deng, Yongkang; Yu, Xinhe; Wei, Xianqin; Zhao, Nianxi; Gao, Yubao; Ren, Anzhi (Frontiers in Plant Science, 2023)
Increases in plant species diversity may increase the community diversity effect and produce community over-yielding. Epichloë endophytes, as symbiotic microorganisms, are also capable of regulating plant communities, but their effects on community diversity are often overlooked. In this experiment, we investigated the effects of endophytes on the diversity effects of host plant communities by constructing artificial communities with 1-species monocultures and 2- and 4-species mixtures of endophyte-infected (E+) and endophyte-free (E-) Achnatherum sibiricum and three common plants in its native habitat, which were potted in live and sterilized soil. The results showed that endophyte infection significantly increased the belowground biomass and abundance of Cleistogenes squarrosa, marginally significantly increased the abundance of Stipa grandis and significantly increased the community diversity (evenness) of the 4-species mixtures. Endophyte infection also significantly increased the belowground over-yielding effects of the 4-species mixtures in the live soil, and the increase in diversity effects was mainly due to the endophyte significantly increasing the belowground community complementary effects. The effects of soil microorganisms on the belowground diversity effects of the 4-species mixtures were mainly derived from their influences on the complementary effects. The effects of endophytes and soil microorganisms on the belowground diversity effects of the 4-species communities were independent, and both contributed similarly to the complementary effects. The finding that endophyte infection promotes belowground over-yielding in live soil at higher levels of species diversity suggests that endophytes may be one of the factors contributing to the positive relationship between species diversity and productivity and explains the stable co-existence of endophyte-infected Achnatherum sibiricum with a variety of plants in the Inner Mongolian grasslands.